ANTIBIOTIC SUSCEPTIBILITY PATTERN OF Vibro species ISOLATED FROM DIARRHOIEC STOOL OF PATIENTS ATTENDING UMARU SANDA GENERAL HOSPITAL, BIDA NIGER STATE, NIGERIA - I. L., MUHAMMAD,; R., BAGUDU,; R. G., MUHAMMAD,; A., MOHAMMED,; J. Z., KASSIM,; N. J., DADI-MAMUD,; D., KUDU, (BIMA JOURNAL OF SCIENCE AND TECHNOLOGY GOMBE, 2021)
The study was carried out to determine the antibiotic susceptibility pattern of Vibrio species isolated from diarrhoeic stool of patients attending Umaru Sanda General Hospital, Bida Niger State, Nigeria between February and March 2018. A total of one hundred and twenty (120) samples were collected from diarrhoeic patients. The diarrhoeic stool samples were analyzed using Thiosulphate citrate bile salt sucrose (TCBS) agar and Muellar-Hinton agar. The isolates were Gram-stained, identified and characterized using biochemical tests. Antibiotic susceptibility test was conducted using the disc diffusion method. The diarrhoeagenic Vibrio species isolated from 120 diarrhoeic stool samples included Vibrio cholerae 16 (59.26%), Vibrio parahaemolyticus 08 (29.63%) and Vibrio vulnificus 03 (11.11%). All the isolates were susceptible to Gentamycin and Ofloxacin but highly resistant to Amoxyclav, Cotrimaxole and Neticillin. The present study revealed that Gentamycin and Ofloxacin could be used as drugs of choice for empirical treatment of diseases associated with Vibrio infection, such as cholera. The bacteria could be called as Amoxyclav-Cotrimaxole-Neticillin resistance Vibrio.